FACTORS ASSOCIATED WITH TURNOVER INTENTION IN WORKERS AT PT. SHIMIZU ADHIKARYA IN 2023 - Marbun, Eka Putri; Arwina. B, Henny (TOUR HEALTH JOURNAL, 2023)
Background: Turnover intention is the desire of workers to quit the company because they move to another company. Companies that have good development programs are the cause of the trigger for someone to change jobs. The high level of turnover intention has now become a serious problem for many companies and even some companies experience frustration when they find out that the recruitment process that has succeeded in attracting qualified staff in the end turns out to be in vain because the recruited staff have chosen jobs in other companies. Purpose: This study aims to determine the factors associated with turnover intention in workers at PT Shimizu Adhikarya. Method: This type of research is quantitative using a cross sectional approach. This research was conducted at PT Shimizu Adhikarya, with a total sample of 35 respondents. This study uses univariate and bivariate analysis. Results: The results of bivariate analysis using Fisher's Exact Test, obtained the results that there is no relationship between workload with a P value of 0.055, no relationship between work stress with a P value of 0.095 and no relationship between the work environment with a P value of 0.450 to turnover intention in workers at PT. Shimizu Adhikarya in 2023. Disscusion and Conclusion: It is suggested to workers to pay attention to workloads that are too heavy and can be useful and experience regarding workload, work stress and work environment on turnover intention, as well as for companies it is hoped that it can help company management as information, consideration and evaluation that can be used for decision making to support the company in a better direction in the future, to further researchers to pay more attention to matters related to workload, work stress and work environment that come both from external, internal, outside or within a company organization, group or individual is an element or matter that must continue to be considered by the company in the future.